Utilization of Rubber Seed Flour (Havea brasiliensis) Fermented with Rhizopusp. As Feed Ingredients for Correcting Freshwater Lobster Seeds (Cherax quadricarinatus) - Simbolon, Lensofa; Adelina, Adelina; Suharman, Indra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on June-July 2019. The purpose of this research was know the percentage of use of fermented rubber seed flour in freshwater lobster seeds to produce feed efficiency and growth of freshwater lobster seeds .  This study uses a completely randomized design (CRD) with one factor, the level 5 treatment and 3 replications. The treatments in this study were fermented rubber seed flour, namely P0 (0%), P1 (10%), P2 (20%), P3 (30%), P4 (40%) in feed.The results showed that the best research was P4. Use fermented formulated rubber seeds in the feed as much as 40%, produce the best freshwater lobster seed growth is 74.8% feed digestibility, digestibility of protein 91.1%, the feed efficiency of 45.88%, retention of protein 52.12%, specific growth rate of 2.32% and survival rate 96.0%.Keyword:,Fermentation, fish feedKeywords: Rubber Seed, Freshwater Lobster (Cherax quadricarinatus), Fermentation, Artificial Feed.